The Effect of Relative Density of Geosynthetic Encased Stone Columns on the Bearing Capacity and Consolidation of Soft Soil - Julita Hayati; Johanes Simamora; Arif Rahman Hakim Sitepu (Borneo Engineering: Jurnal Teknik Sipil, 2026)
Building roads on soft soil is a problem that must be faced due to the behavior of soft soil. The low bearing capacity is the primary issue, accompanied by significant settlement due to the soil's high compressibility. Soft soil is present in the Indrapura-Kisaran Toll Road Construction Project, ranging from STA 111+505 to STA 112+300, so reinforcement is necessary. The reinforcement method used is Geosynthetic Encased Stone Columns (GESC). The density of the GESC material used in this method needs to be examined to determine the effectiveness of GESC in reducing settlement and increasing soil-bearing capacity. The analysis process conducted in this study involves analyzing reinforcement using GESC with empirical and numerical methods. This study uses variations in the relative density of the column material at 25%, 50%, 75%, and 100%. After reinforcement, the soil-bearing capacity increased by 280,37 to 361,71%. Additionally, GESC reinforcement was also able to reduce settlement by up to 64,96% using the analytical method and 41,6% using the numerical method, with a consolidation time reduction of 93,38% to 94,52%. The reduction in relative soil density causes settlement to increase by ±7,2% because the friction angle of the column decreases.